2012
DOI: 10.1177/1362361311431950
|View full text |Cite
|
Sign up to set email alerts
|

Sexual well-being of a community sample of high-functioning adults on the autism spectrum who have been in a romantic relationship

Abstract: This study explored factors (gender, age, relationship status, symptomatology) associated with the sexual well-being of 141 (56 men and 85 women) adults with high-functioning autism and Asperger syndrome (HFA/AS) living in the community. Participants completed an online survey consisting of a measure of autistic symptoms as well as measures of dyadic and solitary sexual well-being. Canonical correlation analyses showed that participants who were currently in a romantic relationship reported more frequent dyadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 43 publications
4
96
2
3
Order By: Relevance
“…Many individuals with ASD express interest in having a sexual relationship [26], are sexually attracted to someone [27], or engage in sexual behavior [28]. Moreover, Gilmour, Schalomon, and Smith [28] did not find significant differences in the breadth and strength of sexual behaviors between individuals with high-functioning ASD and those without ASD.…”
Section: Social Well-being In Relation To Sexualitymentioning
confidence: 96%
See 1 more Smart Citation
“…Many individuals with ASD express interest in having a sexual relationship [26], are sexually attracted to someone [27], or engage in sexual behavior [28]. Moreover, Gilmour, Schalomon, and Smith [28] did not find significant differences in the breadth and strength of sexual behaviors between individuals with high-functioning ASD and those without ASD.…”
Section: Social Well-being In Relation To Sexualitymentioning
confidence: 96%
“…Moreover, Gilmour, Schalomon, and Smith [28] did not find significant differences in the breadth and strength of sexual behaviors between individuals with high-functioning ASD and those without ASD. These data run "counter to social stereotypes that portray individuals with disabilities, including individuals with intact intellect and ASD, as asexual or having sexual behavior problems [26]".…”
Section: Social Well-being In Relation To Sexualitymentioning
confidence: 99%
“…Most studies on sexuality in individuals with ASD, as in the case of the general population, focus on the prevalence of sexual behaviours and on sexual knowledge (Dewinter et al, 2013;Kellaher, 2015). Studies based on self-report (Byers et al, 2012(Byers et al, , 2013Dewinter et al, 2015;Mehzabin and Stokes, 2011;Ousley and Mesibov, 1991) and parental or caregiver reports (Haracopos and Pedersen, n.d.;Hellemans et al, 2007Hellemans et al, , 2010Holmes and Himle, 2014;Stokes and Kaur, 2005) have shown that sexuality is a part of life for individuals with ASD. Especially highfunctioning adolescents and adults with ASD reported or demonstrated interest in relationships and partnered sexuality (Haracopos and Pedersen, n.d.).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found a higher rate of asexuality among men and women with ASD. Byers et al (2012) similarly found higher rates of same-sex attraction when they surveyed ASD individuals who had previously been in a relationship for at least 3 months. Almost 42% of the surveyed adults with ASD endorsed a sexual identity other than heterosexual and 55% stated that they were at least somewhat attracted to both men and women (Byers et al 2012).…”
Section: Sexual Orientation In Asdmentioning
confidence: 95%
“…The social interaction and communication deficits inherent in ASD can lead to later difficulty in forming friendships and close romantic relationships (Byers et al 2012;Carrington et al 2003;Howlin et al 2000;Mehzabin and Stokes 2011). Few studies have been conducted regarding partnered sexuality and ASD, and currently little more is known about partnered sexuality and relationships in individuals with ASD.…”
Section: Sexual Behavior In Asdmentioning
confidence: 99%